Internalisasi Nilai-Nilai Sosial Religius Bagi Anak Tunalaras di SLB E Prayuwana Yogyakarta - Husna, Difaul (Universitas Muhammadiyah Magelang, 2020)
Education does not only prioritize aspects of knowledge and skills, but also pays great attention to personality of the students. But the fact is, some cases of delinquency which are a form of disability, are actually carried out by school-age children. The development that occurs in children with disabilities, is not much different from normal children without disability, but the emotional disturbances they have can affect the child's personality and social. One of schools that handles children with disabilities is SLB-E Prayuwana Yogyakarta. This research can be classified as a descriptive qualitative field research that aims to find out the strategy in internalizing religious social values ​​for children with disabilities at SLB E Prayuwana Yogyakarta, uses observation, interview and documentation techniques. This research was carried out through data reduction, data presentation, verification and data validity testing. Based on research data it is known that internalization of religious social values ​​for children with disabilities in SLB E Prayuwana Yogyakarta is carried out integrated into every activity and subject, religious social culture and habituation program in schools, which prioritizes the compassion approach, as well as collaboration with the education department, parents and communities.